Serum levels of proteins involved in amyloid‐β clearance are related to cognitive decline and neuroimaging changes in mild cognitive impairment. Issue 1 (18th December 2018) - Liu, Shan; Suzuki, Hideaki; Ito, Hitomi; Korenaga, Tatsumi; Akatsu, Hiroyasu; Meno, Kohji; Uchida, Kazuhiko
Abstract: Introduction: Amyloid‐β (Aβ) clearance is important for damage prevention in Alzheimer's disease. We investigated the utility of Aβ clearance proteins as biomarkers for mild cognitive impairment (MCI). Methods: Serum apolipoprotein (apo) A‐I, compliment protein C3 (C3), transthyretin, and cholesterol levels were measured in 273 subjects, and we analyzed the relationship between these levels and brain atrophy and cerebral blood flow in 63 clinically diagnosed mild cognitive impairment, Alzheimer's disease, and nondemented disease control subjects. Results: ApoA‐I and transthyretin levels and the active form of C3:native form of C3 ratio achieved an area under the curve of 0.89 (sensitivity: 83%, specificity: 90%) for detecting late mild cognitive impairment. Atrophy was associated with decreased apoA‐I and high‐density lipoprotein levels. Subjects with reduced cerebral blood flow had lower levels of native form of C3, apoA‐I, high‐density lipoprotein, and total cholesterol. Low native form of C3 and high active form of C3 levels were found in the hippocampi of patients with Alzheimer's disease. Discussion: Aβ clearance proteins in the serum are potential biomarkers for mild cognitive impairment evaluation.